FACTORS INFLUENCING BUSINESS STUDENT’S ENTREPRENEUR’S BUSINESS PERFORMANCE A CASE STUDY OF UGANDA CHRISTIAN UNIVERSITY - ZAKARIA DENG WOL (UGANDA CHRISTIAN UNIVERSITY, 2025)
The study investigated the factors influencing business student’s entrepreneur’s business performance; a case study of Uganda Christian university. The study was guided by the following objectives; To establish the effect of Entrepreneurial skills on student entrepreneurs business performance at Uganda Christian university, to assess the effect of Access to capital on student entrepreneurs business performance at Uganda Christian university and to establish the effect of academic engagement on student entrepreneurs business performance at Uganda Christian university. The study adopted survey research design. The design was used to explain the existence of two or more variables at a given point. Survey research design was useful in this study as it helped to report things the way they are. The study established that entrepreneurial skills and access to capital significantly enhance business performance among student entrepreneurs at UCU, with strong agreement on their importance. However, academic engagement poses challenges, as time spent on business activities can negatively affect academic performance, creating a trade-off. It was concluded that entrepreneurial skills and access to capital are key drivers of student entrepreneurs’ business performance at UCU, while academic engagement poses challenges due to time constraints and institutional policies. These factors collectively shaped the success of student-led ventures, measured by revenue growth, profitability, longevity, and customer satisfaction.
UNDERGRADUATE RESEARCH